Gas Sensing Properties of ZnO-SnO2 Nanocomposite - Kumar, Pushpendra; Kumar, Deepak (Asian Journal of Chemistry, 2019)
In present study, ZnO-SnO2 nanocomposite was synthesized by co-precipitation method and its sensing properties with respect to carbon monoxide gas were investigated. X-ray diffraction pattern shows the exhaustive evolution of hexagonal wurtzite phase of ZnO and rutile phase of SnO2. Morphological study was done by FE-SEM and optical characterization was done by UV-visible spectrophotometer. To study the sensing properties, material was layered on conducting substrate and resistance was recorded in the presence of air and CO gas at different operating temperature. Sensing responses of pure ZnO and ZnO-SnO2 composite was also compared. ZnO-SnO2 showed much enhanced response along with better response and recovery time compared to pure ZnO.